Nerve Growth Factor in Rat Glioma Cells - Longo, Angela M. (1974)
We have shown that rat glioma tumors contain a protein that crossreacts with antibody against mouse 2.5S nerve growth factor prepared in rabbit in microcomplement fixation assays and has analogous isoelectric points to all the hybrids of 2.5S nerve growth factor (a dimer). Partially purified protein preparations from gliomas cause chick dorsal root ganglia to extend neurites in the nerve growth factor assay and cause morphological differentiation of mouse neuroblastoma cells. We conclude that the rat glioma protein is homologous to mouse salivary nerve growth factor and suggest the possibility that glial nerve growth factor plays a role in neuronal development and regeneration.